Cost-effectiveness analysis of human-centred design for global health interventions: a quantitative framework - Liu, Chen; Hyoung Lee, Jae; Gupta, Amanda J.; Tucker, Austin; Larkin, Chris; Turimumahoro, Patricia; Katamba, Achilles; Davis, J, Lucian; Dowdy, David (BMJ Global Health, 2022)
Human-centred design (HCD) is a problem-solving approach that is increasingly used to develop new global health interventions. However, there is often a large initial cost associated with HCD, and global health decision-makers would benefit from an improved understanding of the cost-effectiveness of HCD, particularly the trade-offs between the up-front costs of design and the long-term costs of delivering health interventions. Methods We developed a quantitative framework from a health systems perspective to illustrate the conditions under which HCD-informed interventions are likely to be cost-effective, taking into consideration five elements: cost of HCD, per-client intervention cost, anticipated number of clients reached, anticipated incremental per-client health benefit (ie, disability-adjusted life years (DALYs) averted) and willingness-to- pay. We evaluated several combinations of fixed and implementation cost scenarios based on the estimated costs of an HCD-informed approach to tuberculosis (TB) contact investigation in Uganda over a 2-year period to illustrate the use of this framework. Results The cost-effectiveness of HCD-informed TB contact investigation in Uganda was estimated to vary from US$8400 (2400 clients reached, lower HCD cost estimate) to US$306 000 per DALY averted (120 clients reached, baseline HCD cost estimate). In our model, cost-effectiveness was improved further when the interventions were expected to have wider reach or higher per-client health benefits. Conclusion HCD can be cost-effective when used to inform interventions that are anticipated to reach a large number of clients, or in which the cost of HCD is smaller relative to the cost of delivering the intervention itself.
Keywords: Human-centred design; Global health interventions